Mental Health in Sumatra after the Tsunami - Frankenberg, E.; Friedman, J.; Gillespie, T.; Ingwersen, N.; Pynoos, R.; Rifai, I. U.; Sikoki, B.; Steinberg, A.; Sumantri, C.; Suriastini, W.; Thomas, D. (2012)
Objectives. We assessed the levels and correlates of posttraumatic stress reactivity (PTSR) of more than 20000 adult tsunami survivors by analyzing survey data from coastal Aceh and North Sumatra, Indonesia. Methods. A population-representative sample of individuals interviewed before the tsunami was traced in 2005 to 2006. We constructed 2 scales measuring PTSR by using 7 symptom items from the Post Traumatic Stress Disorder (PTSD) Checklist-Civilian Version. One scale measured PTSR at the time of interview, and the other measured PTSR at the point of maximum intensity since the disaster. Results. PTSR scores were highest for respondents from heavily damaged areas. In all areas, scores declined over time. Gender and age were significant predictors of PTSR; markers of socioeconomic status before the tsunami were not. Exposure to traumatic events, loss of kin, and property damage were significantly associated with higher PTSR scores. Conclusions. The tsunami produced post traumnatic stress reactions across a wide region of Aceh and North Sumatra. Public health will be enhanced by the provision of counseling services that reach not only people directly affected by the tsunami but also those living beyond the area of immediate impact.